Association between psychosocial work-related factors at midlife and arterial stiffness at older age in a prospective cohort of 1736 white-collar workers - Mahée Gilbert-Ouimet; Chantal Brisson; Neil Pearce; Denis Talbot; Alain Milot; Xavier Trudel; Michel Vézina; Victoria K Massamba; Benoît Mâsse; Clermont E Dionne; Gilles R Dagenais (BMJ Open, 2023)
Objective Arterial stiffness and exposure to psychosocial work-related factors increase the risk of developing cardiovascular disease. However, little is known about the relationship between psychosocial work-related factors and arterial stiffness. We aimed to examine this relationship.Design Prospective cohort study.Setting Public organisations in Quebec City, Canada.Participants The study included 1736 white-collar workers (women 52%) from 19 public organisations.Primary and secondary outcome measures Association between psychosocial work-related factors from the job strain and effort–reward imbalance (ERI) models assessed at study baseline (1999–2001) with validated instruments and arterial stiffness assessed using carotid–femoral pulse wave velocity at follow-up, on average 16 years later (2015–2018). Generalised estimating equations were used to estimate differences in arterial stiffness between exposed and unexposed participants. Subgroup analyses according to sex, age, blood pressure (BP), cardiovascular risk score and employment status were conducted.Results Among participants with high diastolic BP (≥90 mm Hg) at baseline, aged 47 on average, those exposed to high job strain had higher arterial stiffness (1.38 m/s (95% CI: 0.57 to 2.19)) at follow-up, 16 years later, following adjustment for a large set of potential confounders. The trend was similar in participants with high systolic BP (≥140 mm Hg) exposed to high job strain (0.84 m/s (95% CI: −0.35 to 2.03)). No association was observed for ERI in the total sample and counterintuitive associations were observed in subgroup analyses.Conclusions Job strain may have a long-term deleterious effect on arterial stiffness in people with high BP. Interventions at midlife to reduce job strain may mitigate arterial stiffness progression.